The Influence of E-Servqual, E-Wom, and E-Trust on Customer Loyalty Through the E-Customer Satisfaction Application of the Darussalam Islamic Boarding School Students, Blokagung Banyuwangi - Nurul Alviah; Diah Yulisetiarini; Hari Sukarno (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Digital transformation in educational services is an important need to improve efficiency and user satisfaction, especially in Islamic boarding schools. One of these innovations is the SISANTRI application used at the Darussalam Blokagung Islamic Boarding School, Banyuwangi, to facilitate the management of information and transactions for guardians of students. However, the effectiveness of this application still faces challenges, such as stagnation in feature development and negative reviews from users.This study aims to analyze the influence of E-Servqual, E-WOM, and E-Trust on E-Customer Satisfaction. Then, analyze the influence of E-Servqual, E-WOM, E-Trust, and E-Customer Satisfaction on customer loyalty. And analyze the role of E-Customer Satisfaction as a mediator of the influence of E-Servqual, E-WOM, and E-Trust on customer loyalty.The research method used is exploratory research and a quantitative approach with data collected through questionnaires distributed to 364 guardians of students selected using the Proportional Stratified Random Sampling technique. The research instrument uses a Likert scale to measure research variables. Then, the collected data is analyzed through several stages, namely determining the value of the variables, testing the research instrument (validity and reliability tests), path analysis using the Partial Least Square (PLS) method, hypothesis testing, and path calculations.The results of the study showed that E-Servqual, E-WOM, and E-Trust significantly influenced E-Customer Satisfaction. In addition, E-Servqual, E-WOM, E-Trust, and E-Customer Satisfaction significantly influenced customer loyalty. Then, customer satisfaction was not able to be a mediating variable between E-Servqual, E-WOM, E-Trust, and customer loyalty, but still contributed to loyalty directly.It can be concluded that improving E-Servqual, E-WOM, and E-Trust is very important to strengthen E-Customer Satisfaction and Customer Loyalty, although E-Customer Satisfaction does not mediate the relationship. Further development should be focused on improving these three main factors that affect customer loyalty.